THE EFFECT OF LEARNING MODELS AND CRITICAL THINKING SKILLS TOWARD MATHEMATICS ACHIEVEMENT BY CONTROLLING STUDENTS’ NUMERIC APTITUDE - NI Nyoman Kawiwati (LPPM Universitas Negeri Jakarta, 2015)
This research is to determine the effect of learning model and critical thinking skills toward mathematics learning achievement of class XI IPA students in senior high school in Gianyar by controlling students’ numeric aptitude. This research used treatment by level 2x2 design and analysis of covariance. The sample was 80 people using multistage random sampling. The results by controlling numeric aptitude are: students learning achievement taught using PAIKEM model is higher than those taught in conventional model. There is an interaction effect between learning model and critical thinking skills toward students’ mathematics achievement. Given high critical thinking skills, students taught using PAIKEM models displayed higher results compared to those in conventional learning who were best in a lower critical thinking skills. Finally, based on the results, it can be recommended to SMA Mathematics teachers to increase students’ Mathematics achievement by using PAIKEM model accurately and to see of students critical thinking skills.